Sexism and Gender Discrimination in Online Divorce Reporting: An Examination of Islamic Family Law Literacy in Jambi, Indonesia - Susi Susanti; Nuzul Iskandar; Darlius Darlius (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2026)
This study examines sexism and gender discrimination in online divorce reporting as an indicator of Islamic family law literacy in online mass media in Jambi, Indonesia. It investigates how media narratives construct the image of women, particularly wives who initiate divorce, and assesses whether such representations reflect an adequate understanding of Islamic family law principles. This study employed Van Dijk’s critical discourse analysis to examine online news articles on divorce published between 2023 and 2025. The analysis focused on diction, narrative structure, and framing strategies used in reporting divorce cases. The findings reveal that online media frequently portray women filing for divorce through stereotypical and discriminatory narratives that reinforce sexist assumptions. These representations not only marginalize women but also demonstrate limited literacy regarding Islamic family law, particularly its principles of justice, balance, and the equal legal rights of spouses in divorce proceedings. The study concludes that gender-biased reporting reflects broader shortcomings in Islamic family law literacy among online media practitioners. Therefore, strengthening journalists' understanding of Islamic family law, together with the adoption of gender-sensitive reporting guidelines, is essential to promote fair, balanced, and legally informed divorce reporting while reducing discriminatory portrayals of women in the public sphere.